Kanoniczna instytucja muzeum kościelnego - Adamczyk, Jerzy (Archiwa, Biblioteki i Muzea Kościelne, 2021)
This article presents the library of the theological seminary in canonical terms. The library of the seminary is an institution which collects, processes and offers readers the collections owned by the seminary. The first part of this article shows the necessity for the seminary library. It then describes the collection of the seminary library, which should contain primarily works in the field of Christian philosophy, psychology, theological sciences and materials necessary for learning foreign languages. It is emphasized that the seminary library is not only a book collection, but also the entire infrastructure, the aim of which is to serve the functioning of the library. The paper also presents those people who are in charge of the seminary library: a diocesan bishop, the rector of the seminary and a librarian, as well as other library staff, both full-time ones and volunteers